2019
DOI: 10.1111/tesg.12368
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Decline and Resilience in Small Towns: Evidence From Three European Case Studies

Abstract: This paper concerns the future of small towns with an old industrial specialisation which have undergone growth processes during the 1900s and now experience de‐industrialisation and identity crises in an economic scenario characterised by the role played by global cities and emerging countries. The concept of resilience has been adopted as the main analytical tool to study this phenomenon. Following an evolutionary approach, resilience is here understood as the dynamic capabilities a system can use to react t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…According to empirical researches, it has been revealed that certain SMEs are temporarily closed due to the negative atmosphere created by the Covid-19 crisis, while others are permanently closed Dai et al, 2021;Egri and Doganer, 2020;, which is projected to increase the poverty rate and the number of extreme poor in communities. Other SMEs trying to survive are found to be unable to pay operating costs, including rent, routine expenses, workers' salaries (Kraus et al, 2020;Lazzeroni, 2020;Le et al, 2020;. The Covid-19 pandemic forced many businesses to close and caused an economic recession unprecedented in most economic activity branches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to empirical researches, it has been revealed that certain SMEs are temporarily closed due to the negative atmosphere created by the Covid-19 crisis, while others are permanently closed Dai et al, 2021;Egri and Doganer, 2020;, which is projected to increase the poverty rate and the number of extreme poor in communities. Other SMEs trying to survive are found to be unable to pay operating costs, including rent, routine expenses, workers' salaries (Kraus et al, 2020;Lazzeroni, 2020;Le et al, 2020;. The Covid-19 pandemic forced many businesses to close and caused an economic recession unprecedented in most economic activity branches.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan ampirik araştırmalara göre belirli KOBİ'lerin Covid-19 krizinin yarattığı olumsuz atmosfer nedeniyle geçici, bazılarının ise kalıcı olarak kapandığı ortaya konulmuştur (Aderemi vd., 2020;Beraha ve Đuričin, 2020;Dai vd., 2021;Eğri ve Doğaner, 2020;Ozcan vd., 2020;, bu durumun da yoksulluk oranını ve topluluklardaki aşırı yoksul sayısını artıracağı öngörülmektedir. Hayatta kalmaya çalışan diğer KOBİ'lerin ise kira, rutin giderler, işçi maaşları dahil olmak üzere işletme maliyetlerini ödeyemedikleri görülmektedir (Kraus vd., 2020;Lazzeroni, 2020;Le vd., 2020;Lu vd., 2020;. KOBİ'lerin bu krizden önemli ölçüde etkilendiğini yapılan araştırma sonuçları da desteklemektedir.…”
Section: Tartışma Ve Sonuçunclassified
“…The scientific achievements of small post-industrial towns are already significant [12,24]. The essence of research in this area focuses primarily on diagnosing the situation in this city after losing the existing functions.…”
Section: Research Reviewmentioning
confidence: 99%
“…ability to attract investments and capacity to create networks on various scales to offset the attraction of large cities, setting value on local 'territorial capitals' (Knox, Mayer 2013;Hamdouch et al 2017b;Lazzeroni 2020).…”
Section: A Heterogeneous Group Of Citiesmentioning
confidence: 99%